PENGARUH PEMBERIAN KOMPOS JERAMI PADI DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KANGKUNG DARAT (IPOMOEA REPTANS POIR) - Zendrato, Yudiwarni; Adiwirman, Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the response of water spinach to rice straw and NPK compost, and looking for a best combination of rice straw and NPK compost that provides the best growth and production of water spinach. This research carried out in the Faculty of Agriculture Experimental Station, Riau University, starting from February 2018 until May 2018. This study used a Randomized Block Design with 2 factors and 3 replications. The first factor was rice straw compost (0, 7 and 14 ton.ha-1) and second factorI namely NPK fertilizer (0, 100 and 200 kg.ha-1). The parameters observed were plant height, leaf number, leaf area, fresh weight, root shot ratio and plant dry weight. Data were analyzed using anova and with HSD 5%. Increasing the dosage of rice straw compost significantly increased plant height, leaf number, leaf area, fresh weight, root to shoot ratio and dry weight of land water spinach. The interaction of giving rice straw compost and NPK fertilizer significantly increased plant height, leaf number, leaf area, fresh weight, and dry weight except the root canopy ratio of land water spinach. The interaction of rice straw compost 14 ton. ha-1 in NPK 200 kg. ha-1 was the best dose to increase plant height, leaf number, leaf area, fresh weight, root canopy ratio and dry weight of land water spinach. Keywords: Ipomoea reptans Poir, rice straw compost and NPK fertilizer